بناء الهوية في الشخصيات الداعمة لرواية ممو زين لسعيد رمضان البوطي: قراءة نفسية في إطار نظرية جاك لاكان - RUSDI, MOHAMMAD ILHAM FAHMI (Ma’dubah : Jurnal Bahasa dan Sastra Arab, 2024)
The purpose of this study is to determine the concept of identity of supporting characters and the factors behind the construction of the identity of supporting characters in the novel "Mamo Zein" by Said Romadlon Al Buthi, with the study of Jacques Lacan’s psychoanalysis. This type of research is descriptive qualitative research. The main data source is the novel "Mamo Zein" by Said Ramadlan Al Buthi, while secondary data sources are books and journals related to the research topic. The researcher used reading and note-taking methods to collect data. To analyze the data, the researcher used data reduction, data presentation, then drew a conclusion based on the identity of the supporting characters using Jaacques Lacan’s theory.Based on the results of this study, two conclusions were obtained: (1) There are 2 characters who experienced all phases, namely Putri Siti and Tajoudin, there are 3 characters who experienced 2 phases, and there is 1 character who experienced only 1 phase. (2) the factors behind the identity construction of supporting characters are internal and external factors including personality, experience, belief and conflict. The conclusion of the results of this study is the symbolic phase in the identity of the supporting character, because in the story in the novel there is a lot about how a person places his position in his desires, including the social environment. The dominating factor is external factors, this proves that identity construction does not only arise from the character’s self, but more appears from outside the character.